Biosuggestive therapy as an effective method for correction and treatment of psychosomatic disorders - Koshyrets, Viktor; Shkarlatiuk, Kateryna (My University, 2022)
The purpose of the article is to describe and analyze the effectiveness of Oleksandr Strazhnyi's biosuggestive therapy, the author's method for the correction and treatment of psychosomatic disorders. Methods. The study examines the method of biosuggestive therapy (MBST) - aimed to remove psychosomatic disorders and restore psychological comfort and well-being of a personality. It includes a combination of verbal and non-verbal suggestion techniques in a light trance state. The method involves the implementation of the following techniques: individual conversation, group conversation (in case of group therapy) and conducting a biosuggestive session. Results. MBST has proven to be one of the most effective psychotherapeutic tools for correcting health disorders using a session consisting of verbal and non-verbal suggestive structures. In the course of the session, the painful nervous processes responsible for the perception of poor health fade away and the neural connections containing the image of well-being are strengthened. As a result, the body's hidden reserves are activated and self-regulation processes are launched. In this way, biosuggestive psychotherapy begins to work according to the laws of a conditioned reflex, that is, a habitual action in response to one or another sensory stimulus. A reflex is fixed with each repeated session and is attached in a long-term memory. Over time, the suggestive blocks voiced by a psychotherapist reprogram a human body to new positive settings. MBST sessions relieve heightened sensitivity to emotional and physical pain. Conclusions. The technique of micro-breaks lies in the basis of biosuggestive psychotherapy. The sudden break of the pattern lies in the fact that a psychotherapist begins the conversation without adjustment, immediately by going beyond the pattern. For this, you can use a positive statement, a positive emotion etc. The meaning of a psychologist's work is to switch sharply a person's attention from emotional trauma, mental or physical pain, to the good, that is, a negative factor to a positive one. The practice of combining the MBST sessions with other therapeutic techniques is also used.
Keywords: біосугестивна терапія; психотерапевтична техніка; терапевтичний ефект; аудіосеансна музика; техніка мікророзривів; сеанс біосугестії; терапевтичний дотик; biosuggestive therapy; psychotherapeutic technique; MBST therapeutic effect; audio session music; micro-breaks technique; biosuggestive session; therapeutic touch; 159.964.225:615]:616.89:611.9